Effect of Health Educational Guidelines on Self-Management Practices among Patients with Chronic Obstructive Pulmonary Disease: A Scoping Review - Eman R. Alharbi; Samah M. Sofar; Dhuha Y. Wazqar (Evidence-Based Nursing Research)
Context: Chronic obstructive pulmonary disease (COPD) is a type of lung disease characterized as chronic lung airflow obstruction that interferes with normal respiration. The World Health Organization ranked it as the third leading cause of death. The evidence indicates that health education may improve patients' outcomes.